Studi Literatur Pengembangan Media Interaktif pada Materi Vektor - Yenni Novita Harahap; Dian Fatma Diva; Juli Andriyani; Melani Prasiska; Talitha Eriliyah Wardhana Lumban Tobing; Sakdiah Aini Rangkuti; Abdul Razaky Irani (Journal on Education, 2023)
Interactive media is an important component in educational activities, particularly in the fourth industrial revolution age. Teachers utilize learning material to support effective and efficient learning and to improve understanding among pupils. There is a need for a revolution in the learning material utilized by educators in the digital era. The media should not only be entertaining, but it should also be capable of developing higher-order thinking abilities in kids. Through its comprehensive design, including user instructions, content, and evaluation, interactive media, in particular, has the potential to make instructors' jobs easier and promote autonomous learning among students. Given these factors, a study of interactive media in the fourth industrial revolution is required. The purpose of this study is to see if interactive media in the fourth industrial revolution may impact students' learning results. This study's research technique is a literature review based on several publications.